Endothelial platelet-derived growth factor-mediated activation of smooth muscle platelet-derived growth factor receptors in pulmonary arterial hypertension. (September 2020) - Wu, Kang; Tang, Haiyang; Lin, Ruizhu; Carr, Shane G.; Wang, Ziyi; Babicheva, Aleksandra; Ayon, Ramon J.; Jain, Pritesh P.; Xiong, Mingmei; Rodriguez, Marisela; Rahimi, Shamin; Balistrieri, Francesca; et al.
Platelet-derived growth factor is one of the major growth factors found in human and mammalian serum and tissues. Abnormal activation of platelet-derived growth factor signaling pathway through platelet-derived growth factor receptors may contribute to the development and progression of pulmonary vascular remodeling and obliterative vascular lesions in patients with pulmonary arterial hypertension. In this study, we examined the expression of platelet-derived growth factor receptor isoforms in pulmonary arterial smooth muscle and pulmonary arterial endothelial cells and investigated whether platelet-derived growth factor secreted from pulmonary arterial smooth muscle cell or pulmonary arterial endothelial cell promotes pulmonary arterial smooth muscle cell proliferation. Our results showed that the protein expression of platelet-derived growth factor receptor α and platelet-derived growth factor receptor β in pulmonary arterial smooth muscle cell was upregulated in patients with idiopathic pulmonary arterial hypertension compared to normal subjects. Platelet-derived growth factor activated platelet-derived growth factor receptor α and platelet-derived growth factor receptor β in pulmonary arterial smooth muscle cell, as determined by phosphorylation of platelet-derived growth factor receptor α and platelet-derived growth factor receptor β. The platelet-derived growth factor-mediated activation of platelet-derived growth factor receptor α/platelet-derived growth factor receptor β was enhanced in idiopathic pulmonary arterial hypertension-pulmonary arterial smooth muscle cell compared to normal cells. Expression level of platelet-derived growth factor-AA and platelet-derived growth factor-BB was greater in the conditioned media collected from idiopathic pulmonary arterial hypertension-pulmonary arterial endothelial cell than from normal pulmonary arterial endothelial cell. Furthermore, incubation of idiopathic pulmonary arterial hypertension-pulmonary arterial smooth muscle cell with conditioned culture media from normal pulmonary arterial endothelial cell induced more platelet-derived growth factor receptor α activation than in normal pulmonary arterial smooth muscle cell. Accordingly, the conditioned media from idiopathic pulmonary arterial hypertension-pulmonary arterial endothelial cell resulted in more pulmonary arterial smooth muscle cell proliferation than the media from normal pulmonary arterial endothelial cell. These data indicate that (a) the expression and activity of platelet-derived growth factor receptor are increased in idiopathic pulmonary arterial hypertension-pulmonary arterial smooth muscle cell compared to normal pulmonary arterial smooth muscle cell, and (b) pulmonary arterial endothelial cell from idiopathic pulmonary arterial hypertension patients secretes higher level of platelet-derived growth factor than pulmonary arterial endothelial cell from normal subjects. The enhanced secretion (and production) of platelet-derived growth factor from idiopathic pulmonary arterial hypertension-pulmonary arterial endothelial cell and upregulated platelet-derived growth factor receptor expression (and function) in idiopathic pulmonary arterial hypertension-pulmonary arterial smooth muscle cell may contribute to enhancing platelet-derived growth factor/platelet-derived growth factor receptor-associated pulmonary vascular remodeling in pulmonary arterial hypertension.